Disability and Education: Between the Corporality That Disables and the Right to Have Rights - Rodolfo Cruz-Vadillo; Paulina Iturbide-Fernández (Universidad Nacional, Costa Rica, 2018)
This article is the result of an investigation whose main purpose was to analyze the constructions of the concept of disability. We intend to analyze the discourses on disability that teachers working with students in this situation have built. The approach to the data was from a qualitative paradigm, of descriptive scope, and supported by the grounded theory methodology. Questionnaires were applied to 22 participants, basic education teachers. We conclude that the scientific knowledge has hegemonized visions, but in the process it has turned to common sense, leaving aside an important substratum as it is our action in front of other people and the consequences of the interventions and diagnoses that, being scientifically validated, invalidate the others and exclude the others. The above implies looking at teacher training from an ethical and political stage where complex processes of reflection overcome the reduced vision that has been built on disability and its inclusion.